The Camorra Comedy: Naples in the (Post-)National Cinematic Gaze. (4th May 2019) - Glynn, Ruth
ABSTRACT: This article addresses the contemporary Camorra comedy film with reference to the transition from a predominantly local to an increasingly national cinematic gaze on Naples. Focusing on Paola Randi's Into paradiso (2010) and the Manetti Bros.' Song 'e Napule (2013), and drawing on theoretical frameworks relating to post-national and accented cinema, as well as to the nexus between national identity and masculinity, it asks what role comedy plays in the national film industry construction of Naples and its relationship with the Camorra. I argue that Into Paradiso 's overt projection of a post-national consciousness is diluted by its recourse to problematic historical discourses and stereotypes relating to the Italian south and its blindness to subnational inflections of Italianness. In contrast, Song 'e Napule 's rehabilitation of Neapolitan popular culture on the part of the anti-Camorra struggle encourages a broad reframing of the discussion of Italian national culture in the terms of differently accented practices, discourses, and identities.